(untitled) (UNED Research Journal, 2016)
In Southeastern Mexico, aquaculture has been seriously affected by the high costs of commercial food. As part of the search for alternative foods we tested the freshwater fish Astyanax aeneus and the snail Pomacea flagellata as possible protein sources for Cichlasoma urophthalmus. We applied fluoxymesterone androgenic hormone for 45 days. One kilogram of experimental food (P. flagellate/A. aeneus) and one of commercial food were sprayed with solution of fluoxymesterone/absolute ethanol, at 5mg/L/kg rate (hormone/alcohol/food). The experimental and artificial foods (THA and SHC, respectively) were tested in fry C. urophthalmus,synchronously with their control groups (TA and SC, respectively), by triplicate. THA produced the highest specific growth and final mean weight (p<0.05). There were differences in sex ratios but considering the dosage they are not relevant.